ESTUDO DE ESPAÇAMENTOS NA CULTURA DO GUANDU. IV – EFEITOS NA PRODUÇÃO DE SEMENTES E NOS COMPONENTES DA PRODUÇÃO - Marchi, Maria José de; Nakagawa, João; Machado, José Ricardo (REVISTA DE AGRICULTURA, 2015)
ESTUDO DE ESPAÇAMENTOS NA CULTURA DO GUANDU. IV – EFEITOS NA PRODUÇÃO DE SEMENTES E NOS COMPONENTES DA PRODUÇÃO